Awer Honey-Hunting Culture With Greater Honeyguides in Coastal Kenya - van der Wal, Jessica E. M.; Gedi, Isa I.; Spottiswoode, Claire N. (Frontiers in Conservation Science, 2022)
The remarkable mutualism between humans and greater honeyguides (Indicator indicator) is known still to thrive in only a few places in Africa. Here, we report on the honey-hunting culture of the marginalised Awer people in Kenya, historically a hunter-gatherer culture who today practice a mixed economy including significant amounts of foraging for wild foods. As part of a larger effort to document cross-cultural honey-hunting traditions in Africa, we interviewed six Awer honey-hunters to document their cultural practices. The interviewees reported that they depend on wild honey as a source of income, and that they readily seek the cooperation of honeyguides. Honey-hunting skills and the calls/whistles used to communicate with honeyguides are learned from their fathers and other elders in village. The best time to honey-hunt is in the months following the big rains (August–December), when interviewees go out honey-hunting once a week on average. Honeyguides are not actively rewarded with wax, as it is believed that once a bird is fed it will not cooperate again for some time, and therefore after the honey harvest is complete, all remaining wax comb is buried. Honey-hunting practices are declining in this region, which interviewees attributed to drought and a lack of interest by the youth. These findings expand our understanding of how human-honeyguide mutualism persists across a range of human cultural variation.